Avaliação das metodologias de ventilação natural da normalização brasileira de desempenho térmico e eficiência energética de edificações habitacionais - Daniel de Oliveira Amaral (2017)
In a country like Brazil, with mild climate in a large part of its territory, natural ventilation in dwellings has great potential to contribute to thermal comfort of its habitants, and with energy efficiency of these buildings. It is essential the correct design of building envelope to the climate to which it is exposed and the right dimensioning of natural ventilation. The aims of this dissertation are: to identify national and international building ventilation standard’s parameters and natural ventilation prediction methods; an average theoretical model development of different urban densification situations; an analysis using computational simulation if the compliance with Brazilian standards assures thermal comfort; and a natural ventilation design guideline definition for thermal comfort based in air change per hour. It was generated low-rise and high-rise densification theoretical models with constant and variable building heights, and was used a social interest building model with climate optimized envelope to internal analysis. CFD simulations allowed the analysis of proposed high-rise models and obtaining pressure coefficients over studied building façade. These data fed thermal energy simulations to Belo Horizonte climate using Airflow Network model that had as outputs hourly internal operative temperatures and air change per hour. As results, it was observed that the high-rise densification model with different building heights reproduces better wind flow and coefficient pressure values over façades compared to results found in the literature review. The studied building is well evaluated according Brazilian standards NBR 15.575:2013 and RTQ-R, diverging from the results of hours in thermal comfort obtained in the case of study. A low correlation between air change per hour and internal operative temperature doesn’t allowed the definition of air change per hour guidelines rate for thermal comfort. It is expected this work has contributed to the discussion about design parameters, normative or not, that aid natural ventilation dimensioning providing thermal comfort in dwellings to its users.